Animal welfare and the paradox of animal consciousness - Dawkins, M (Elsevier, 2015)
Consciousness has always been both central to and a stumbling block for animal welfare. On the one hand, the belief that nonhuman animals suffer and feel pain is what draws many people to want to study animal welfare in the first place. Animal welfare is seen as fundamentally different from plant “welfare” or the welfare of works of art precisely because of the widely held belief that animals have feelings and experience emotions in ways that plants or inanimate objects - however valuable - do not (Midgley, 1983; Regan, 1984; Rollin, 1989; Singer, 1975). On the other hand, consciousness is also the most elusive and difficult to study of any biological phenomenon (Blackmore, 2012; Koch, 2004). Even with our own human consciousness, we are still baffled as to how the wealth of subjective experience we all know from first-hand experience can actually arise from a lump of nervous tissue weighing less than 2 kg. Unable to understand our own consciousness, we are even more at a loss when it comes to its possible existence in other species (Dawkins, 2012). There is thus a seeming paradox at the heart of a science of animal welfare (Dawkins, 1980; Fraser, 2008). To be comprehensive enough to include what most people mean by animal welfare, it must involve understanding what animals consciously feel and experience. But to be a science, it has to embrace the one thing that biology currently finds very difficult, if not impossible to study, namely, animal consciousness. Generally speaking, there are four different ways of dealing with this paradox that can be found among people who all call themselves animal welfare scientists <orderedlist> <listitem> 1. Animal consciousness is not a problem for scientific study. There is therefore no paradox. </listitem> <listitem> 2. Animal consciousness is a problem for scientific study but although we cannot study it directly, we can do the next best thing and study the behavioral and physiological correlates of it. </listitem> <listitem> 3. Animal consciousness is problematic at the moment because we do not yet have the right research methods for studying it. However, with more research we will solve this problem and so the paradox will disappear. </listitem> <listitem> 4. Animal consciousness is likely to remain beyond scientific methods for the foreseeable future but solving it is not central to a scientific study of animal welfare. The paradox therefore exists but it does not matter. </listitem> </orderedlist> These views are clearly very different from each other and reflect fundamentally different ideas about animal consciousness and therefore what the aims of a science of animal welfare should be. This article examines how animal welfare science has dealt with the problem of animal consciousness and whether it has successfully resolved the paradox.